2003
DOI: 10.1097/00002030-200307040-00013
|View full text |Cite
|
Sign up to set email alerts
|

Response to highly active antiretroviral therapy strongly predicts outcome in patients with AIDS-related lymphoma

Abstract: Efficacy of HAART was independently associated with prolonged survival in this large cohort of patients with ARL. Information on patient's response to HAART is crucial for the evaluation of future treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
74
2
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 42 publications
7
74
2
6
Order By: Relevance
“…Some studies have reported that patients with Hodgkin's lymphoma (HL) or non-Hodgkin's lymphoma (NHL) who started cART at the same time as chemotherapy showed increased survival [54][55][56], reduced toxicity (especially bone marrow toxicity), and a decreased risk of developing opportunistic infections. Therefore, cART should be started before or at the same time as chemotherapy in patients diagnosed with HL, NHL, or Kaposis's sarcoma (A-I).…”
Section: (C-i)mentioning
confidence: 99%
“…Some studies have reported that patients with Hodgkin's lymphoma (HL) or non-Hodgkin's lymphoma (NHL) who started cART at the same time as chemotherapy showed increased survival [54][55][56], reduced toxicity (especially bone marrow toxicity), and a decreased risk of developing opportunistic infections. Therefore, cART should be started before or at the same time as chemotherapy in patients diagnosed with HL, NHL, or Kaposis's sarcoma (A-I).…”
Section: (C-i)mentioning
confidence: 99%
“…Sin embargo, se ha observado un incremento de neoplasias no asociadas a síndrome de inmunodefi ciencia adquirida (SIDA) como el linfoma de Hodgkin (LH), cáncer anal, pulmón, cabeza y cuello y conjuntiva [1][2][3] . El uso de TARV ha mejorado el pronóstico de pacientes con linfoma debido a la reconstitución inmunológica [4][5][6][7][8] , aunque la sobrevida es signifi cativamente menor que en pacientes seronegativos, debido a una menor tolerancia a drogas inmunosupresoras, mayor posibilidad de efectos adversos y mayor riesgo de infecciones 1,9,10 . El objetivo de este estudio fue analizar las características clínicas, tratamiento, sobrevida y factores pronósticos, de pacientes seropositivos con linfoma, diagnosticados y tratados en el Hospital del Salvador, centro de referencia del Area Oriente de la Región Metropolitana de Santiago, I, II y III regiones del país, donde se controlan alrededor de 1.500 pacientes con TARV.…”
unclassified
“…10 These findings may be attributable both to specific cancer characteristics in HIV-infected individuals (a more aggressive behavior and an advanced stage at diagnosis) [6][7][8]11,12 and to subject characteristics (immunodeficiency, low performance status). The use of HAART improved short-and medium-term survival in HIV-infected patients with cancer, 8 especially those with ADM [13][14][15] and some types of NADM (e.g., HD) 16,17 and reduced the difference from the general population. 8 However, very few studies described 10-year survival in patients with HIV and cancer, and the only published data are limited to subjects with NHL, Kaposi's sarcoma (KS), and anal cancer.…”
mentioning
confidence: 99%